Thermoplastic-modified epoxy resins cured with different functionalities amine mixtures: Morphology, thermal behavior, and mechanical properties - Blanco, Miren (2009)
Epoxy matrices inherent brittleness and poor crack resistance make necessary some form of toughening.In this work, to improve their fracture toughnessand ductility epoxy matrices were modified by changing its architecture and by the addition of a third component.The matrices architecture were modified by stoichiometrically reacting a bifunctional epoxy resin with differentfunctionalities amine mixtures, one of which being a monoamine that plays the role of chain extender. In the modificationby the addition of a third component, poly(methylmethacrylate) (PMMA) was selected as modifier. PMMA isinitially miscible with epoxy/amine systems but can phase separate during curing. The kinetics and miscibility of these systems were studied previously. At constant curingconditions, materials from completely opaque (phase separated) to transparent (miscible) can be obtained with theincrease in monoamine content. In this work, the effects of the modifier content and of the monoamine : diamine ratioin stoichiometric epoxy/amine mixtures on the resultant morphologies as well as on their thermal and mechanical properties was studied.